Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype - Shaul Lerner; Raya Eilam; Lital Adler; Julien Baruteau; Topaz Kreiser; Michael Tsoory; Alexander Brandis; Tevie Mehlman; Mina Ryten; Juan A. Botia; Sonia Garcia Ruiz; Alejandro Cisterna Garcia; et al. (Human Genetics, 2021)
Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyrosine aggregates, in elevation of α-synuclein, and phenotypically in motor and cognitive deficits. NO supplementation rescues the formation of aggregates as well as the motor deficiencies. Our data point to a potential metabolic link between accumulations of tyrosine and seeding of pathological aggregates in neurons as initiators for the pathological processes involved in neurodegeneration. Hence, interventions in tyrosine metabolism via regulation of NO levels may be therapeutic beneficial for the treatment of catecholamine-related neurodegenerative disorders.

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Assessing the availability of life cycle assessments in Austria - A. O. Ladenika; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

Review: the availability of life-cycle studies in Sweden - Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

The availability of life-cycle assessment, water footprinting, and carbon footprinting studies in Brazil - Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

A discussion on the availability of life-cycle assessment studies in New Zealand - Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Review: life-cycle assessment, water footprinting, and carbon footprinting in Portugal - Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Review: life cycle assessments in Nigeria, Ghana, and Ivory Coast - Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2017)

Erratum to: Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Complete genome sequence of Colocasia bobone disease-associated virus, a putative cytorhabdovirus infecting taro - Colleen M. Higgins; Nicolas Bejerman; Ming Li; Anthony P. James; Ralf G. Dietzgen; Michael N. Pearson; Peter A. Revill; Robert M. Harding (Archives of Virology, 2016)

Rapana venosa as an indicator species for TBT exposure over decadal and seasonal scales - Juliana M. Harding; Michael A. Unger; Roger Mann; E. Alex Jestel; Catherine Kilduff (Marine Biology, 2013)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Lidar remote sensing of above‐ground biomass in three biomes - Michael A. Lefsky; Warren B. Cohen; David J. Harding; Geoffrey G. Parker; Steven A. Acker; S. Thomas Gower (Global Ecology and Biogeography, 2002)
Estimation of the amount of carbon stored in forests is a key challenge for understanding the global carbon cycle, one which remote sensing is expected to help address. However, estimation of carbon storage in moderate to high biomass forests is difficult for conventional optical and radar sensors. Lidar ( li ght d etection and r anging) instruments measure the vertical structure of forests and thus hold great promise for remotely sensing the quantity and spatial organization of forest biomass. In this study, we compare the relationships between lidar‐measured canopy structure and coincident field measurements of above‐ground biomass at sites in the temperate deciduous, temperate coniferous, and boreal coniferous biomes. A single regression for all three sites is compared with equations derived for each site individually. The single equation explains 84% of variance in above‐ground biomass ( P

The relationship of BRMS1 and RhoGDI2 gene expression to metastatic potential in lineage related human bladder cancer cell lines - M. Jabed Seraj; Michael A. Harding; John J. Gildea; Danny R. Welch; Dan Theodorescu (Clinical & Experimental Metastasis, 2000)

Prognostic Markers in Localized Prostate Cancer: From Microscopes to Molecules - Michael A. Harding; Dan Theodorescu (Cancer and Metastasis Reviews, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)